Blood Lead and High-Density Lipoprotein Concentrations in Relation to Human Blood Pressure: A Cross Sectional Study - Hu, Biao; He, Pei-yao; Zhong, Nan-nan; Gao, Zi-min; Guo, Jiang-long; Feng, Jun-tao; Huang, Chu-qin; Yang, Jun-bo; Sun, Dong-lin (Frontiers in Nutrition, 2022)
Background: While the relationship between blood pressure and blood lead has been studied more extensively, the effect of high-density lipoprotein (HDL) concentration on this relationship remains uncertain. Therefore, this study aimed to determine the effect of HDL concentration on the relationship between blood lead and blood pressure. Methods: The research used cross-sectional data fro m the 2005-2014 National Health and Nutrition Examination Survey (NHANES), which included 16,451 participants aged 20-60 years. Multivariable linear regression was used to evaluate the correlation among blood lead, systolic blood pressure (SBP), and diastolic blood pressure (DBP).  HDL concentration was determined by low HDL concentration (≤49mg/dl) and high HDL concentration (>49mg/dl) stratified. The effect of HDL concentration was assessed by an interaction test between blood lead and SBP in multivariable linear regression. Results: In this cross-sectional research, we identified a positive correlation between blood lead and SBP, but not DBP. The relationship between blood lead and SBP was different in the group with low and high HDL concentrations (β:0.21 95%Cl: -0.05-0.46 vs β:0.47 95%Cl: 0.15-0.79). In addition, high HDL significantly altered the positive correlation between blood lead and SBP (P-value of interaction < 0.001). Conclusion: The study suggests an interaction between HDL and blood lead in elevating SBP, which may have important clinical implications.